THE DIAGNOSTIC PROFILES OF HARMFUL EFFECTS OF TETRABROMOETHANE LONG INHALATION IMPACT - A. S. Ogudov; G. P. Ivleva; G. A. Korotaeva; E. V. Rezanova; N. A. Zubtsovskaya (Сибирский научный медицинский журнал, 2019)
The purpose of the study was to provide of diagnostic profiles of harmful effects caused by long inhalation of 1,1,2,2-tetrabromoethane (TBE). Material and methods. The object of research was white rats exposed to the roundthe-clock inhalation of TBE within three months. The TBE concentration in air samples from exposure chambers was determined by means of the Agilent 7890 B chromatograph (France). Urine analysis and biochemical blood test were conducted by means of the standard and unified laboratory methods. Results and discussion. TBE inhalation (concentration 0.2 ± 0.01, 0.6 ± 0.03 and 1.8 ± 0.07 mg/m3) leads to structural and functional changes in target organs. The expressiveness and the changes range grew with the toxic effect level increase. We have defined group of deviations of biochemical indicators connected with the mechanism of toxic action and pathological changes in target organs. When planning clinical trials with high probability it is necessary to expect the diagnoses relating to critical organs and systems – nervous system, liver and kidneys.